Augmented Reality Media Development on Human Excretory System Material to Improve Digital Literacy and HOTS - Baskoro Adhiguna; Sri Yamtinah; Muzzazinah Muzzazinah (PAEDAGOGIA, 2025)
Excretory system material is one of the materials that is difficult to understand the concept because it has a lot of memorization, terms, and mechanisms. Excretory system material is less preferred and tends to be boring because it requires students to memorize terminology and Latin language to introduce organs involved in the human excretion process. The use of learning media integrated with AR technology can be an effective solution in improving learning. Through this technology, various abstract concepts that are usually invisible can be displayed in 3D or 2D, making them appear more real. This study aims to assess the feasibility, practicality, and effectiveness of AR-based learning media on human excretory system material to improve HOTS and digital literacy of grade VIII junior high school students. This research uses the ADDIE development model with a pretest-posttest control group design. The study used control and experimental classes with a total sample of 140 students. The instruments used were questionnaires and tests of digital literacy and HOTS. Data analysis included descriptive and inferential statistics. The results showed that AR media was feasible, with media and material expert assessments based on the Aiken index of 0.909 and 0.835. Practicality scores from teachers and students received scores of 90.62% and 91.12%. N-Gain test showed a substantial increase, and the one-way manova test showed statistical significance (p < 0.05). The AR media developed has met the values of feasibility, practicality, and effectiveness in improving digital literacy and HOTS.